ANALISIS KARAKTERISTIK HIDROLOGI TERHADAP POTENSI SUMBER DAYA AIR BERDASARKAN ANALISA BMKG RCP 4.5 DI DAS SEJAHTERA, SULAWESI TENGAH - Suhudi Suhudi; Kiki Frida Sulistiyani; Ratnasari Rambu Dulu Mosa (BUANA SAINS, 2023)
The Sejahtera River Basin is located in Sejahtera Village, Palolo District, Sigi Regency, Central Sulawesi with an area of 61,028 Ha. The watershed is one of the water resources used for rice field irrigation for the people in the area. The aimed of this study to determine the hydrological characteristics and how much reliable discharge is available in the Sejahtera Watershed for existing conditions and due to climate change. In 2003–2020 an analysis of hydrological characteristics was carried out and there was an increase in the reliable discharge of 20% or 24 l/sec caused by climate change in the Sejahtera Watershed where the rains became lighter with an increase in presentation capacity ranging from 0–10 and 11-20% with moderately increasing temperatures ranging from 0.65-0.70 and 0.71 – 0.75oC. The data used in this research is secondary data. The condition of the Prosperous Watershed is still quite good, so it needs to be maintained so that there are no changes in land use.